Taâ€™thÄ«r IstikhdÄm al-Biá¹Äqah al-Wamá¸iyah bi al-á¸¤urÅ«f al-HijÄâ€™iyyah fÄ« IstÄ«Ê¿Äb al-MufradÄt al-Ê¿Arabiyyah - Latif, Nabil (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Lack of vocabulary is a problem while learning a language for non-native speakers since it results in speech weakness. Due to their inability to comprehend what they were being taught and lack of enthusiasm, the pupils found it difficult to regurgitate the terminology. The Alphabet Flash Card Tool was created to make learning enjoyable. In addition to graphical features, it is a device that makes it simpler for pupils to comprehend the lesson so they can obtain better outcomes (writing and pictures). Quantitative field research, an experimental design, and statistical methods are the research techniques used. After conducting the post-test comparing the two groups in this study, the researcher discovered the results: the experimental class had an average score of (77,5), while the control class had an average score of (65,90). The researcher discovered a result that is superior to the result in the table (Tt) in the degree of 5% = 1.99 and has a t-test result (To) = 2.36. Finally, the second semester vocabulary comprehension of the pupils at Muhammadiyah Langsa Intermediate School is affected by the use of the alphabetical flashcardsÙ‚Ù„Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¹Ù†Ø¯ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙŠØ³Ø¨Ø¨ Ø¶Ø¹Ù ÙÙŠ Ø§Ù„ÙƒÙ„Ø§Ù…. ÙˆÙƒØ°Ù„Ùƒ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø¶Ø¹Ù ÙÙŠ Ù†Ø·Ù‚ Ø§Ù„ØØ±ÙˆÙ Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¨Ø³Ø¨Ø¨ Ø°Ù„Ùƒ ÙˆØ¬Ø¯ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµØ¹ÙˆØ¨Ø© ÙÙŠ ØªÙƒØ±Ø§Ø± Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙˆÙ‚Ù„Ø© Ø§Ù„ÙÙ‡Ù… ÙˆÙ‚Ù„Ø© Ø±ØºØ¨Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ø£Ø¯Ø§Ø© Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„ÙˆÙ…Ø¶ÙŠØ© Ø¨Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© ÙŠØ¬Ø¹Ù„ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù…ØªØ¹Ø©. Ù‡ÙŠ Ø¢Ù„Ø© ØªØ³Ù‡Ù„ Ø¹Ù„Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙ‡Ù… Ø§Ù„Ø¯Ø±Ø³ ØØªÙ‰ ÙŠØªÙ…ÙƒÙ†ÙˆØ§ Ù…Ù† ØªØÙ‚ÙŠÙ‚ Ù†ØªØ§Ø¦Ø¬ Ø£Ø¹Ù„Ù‰ØŒ Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø±Ø§ØØ© Ø§Ù„Ø±Ø³ÙˆÙ…ÙŠØ© Â ÙŠØ¹Ù†ÙŠ ØªØ¯Ø±ÙŠØ¨ Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø¨Ø§Ù„ØµÙˆØ±. ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù… Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ÙŠØ¯Ø§Ù† Ø§Ù„ÙƒÙ…ÙŠ Ø¨Ø§Ù„Ù†ÙˆØ¹ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØŒ ÙˆØ¨Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥ØØµØ§Ø¦ÙŠØ©. ÙˆØ§Ù„Ù†ØªÙŠØ¬Ø© Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ ÙˆØ¬Ø¯ Ø§Ù„Ø¨Ø§ØØ« ØªØ£Ø«ÙŠØ± Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„ÙˆÙ…Ø¶ÙŠØ© Ø¨Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© ÙÙŠ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§ØªØŒ ÙˆÙ…Ù† Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø¨Ø¹Ø¯ Ø£Ù† Ù‚Ø§Ù… Ø¨Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ Ø¨ÙŠÙ† ÙØµÙ„ÙŠÙ†: ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ø¨Ø§Ù„Ù…Ø¹Ø¯Ù„ (77,5) ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø·ÙŠ Ø¨Ø§Ù„Ù…Ø¹Ø¯Ù„ (65,90). ÙÙˆØ¬Ø¯ Ø§Ù„Ø¨Ø§ØØ« Ù†ØªÙŠØ¬Ø© Ø¨Ø§Ø®ØªØ¨Ø§Ø±-Øª (To) = 2,36 Ø£ÙƒØ¨Ø± Ù…Ù† Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„Ø¬Ø¯ÙˆÙ„ (Tt) ÙÙŠ Ø§Ù„Ø¯Ø±Ø¬Ø© 5%= 1,99. ÙˆØ§Ù„Ø®Ù„Ø§ØµØ©ØŒ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„ÙˆÙ…Ø¶ÙŠØ© Ø¨Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© Ù„Ù‡Ø§ Ø¢Ø«Ø§Ø± ÙÙŠ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨Â  ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ù…ØÙ…Ø¯ÙŠØ© Ù„Ø§Ù†Ø¬Ø³Ø§.